The Oral History of the Portuguese Jewish Community in the XXI Century: Family Histories and Life Stories of Three Generations in Portugal - Carvalho, X. (SOAS Centre for Jewish Studies Evening Lectures Series, 2015)
My presentation will draw on the oral history of the Portuguese Jewish Communityin XXI century using family histories and life stories of three generations in Portugal,particularly from the Jewish Community of Lisbon. The images that you are seeinghere are from the synagogue of Lisbon, called “Shaaré Tikva” or ‘Gates of Hope’,from the beginning of the XX century, that has a symbolic meaning in the history of the Portuguese Jewish Community in a country that is mainly Catholic by religion.This synagogue is a reflex of the social and historical relationship that wasdeveloped over centuries: the synagogue is in one of the main streets of the capitalcity, but at the time it could not be visible from the street because it was notCatholic.Today I will present the outcome of an anthropological, sociological and historicalstudy over three generations of Portuguese Jews, especially focused on the historyof the Sephardim and Ashkenazim in and out of Portugal from the XV century untilthe present day.I used an ethnographic methodology, doing an extensive ethnographic fieldwork fortwo years, that allowed me to do an oral reconstruction of their life stories andfamily memories until modern times, debating issues such as nation, belonging,religion and the meaning of being a Portuguese Jew nowadays. The reconstruction of their history is done taking in account the national and transnational narratives of Europe, Middle-East,Africa and America.It is my intention to contribute for an understanding of the national identity inPortugal and within Europe in a time when questions such as the right of belongingor living is becoming an importantpart of the publicand private discourses